Respons penerima manfaat terhadap program pemberdayaan ekonomi masyarakat dhuafa (P2EMD) bidang peternakan di Gampong Kajhu, Baitussalam, Aceh Besar (Beneficiaries' responses to the economic empowerment program for the poor (P2EMD) in the livestock sector in Kajhu Village, Baitussalam, Aceh Besar) - Daud, Muhammad; Usman, Yunasri; Arismawan, A (Universitas Syiah Kuala, 2022)
The service activity of economic empowerment program for dhuafa community (P2EMD) in livestock sector aimed to empower the poor community in the livestock business sector by providing productive business capital assistance in the form of livestock sourced from the Rumah Amal (Charity House) of Universitas Syiah Kuala. Technically, this P2EMD service was introduced to the poor as many as 7 beneficiaries who needed help and were right on a target located in Kajhu Village, Baitussalam Sub-District, Aceh Besar District. The approach methods used during the realization period were the provision of knowledge on the use of business capital, economic empowerment in the livestock sector, assistance and development of livestock business, and evaluation/response of beneficiaries. The results of this service showed a good and positive response from the beneficiaries. In addition, the beneficiaries understood very well the importance of the sustainability of the P2EMD program in the future. Overall, the beneficiaries will continue and develop the business capital that has been received on a larger and more feasible business scale.